Legionella pneumophila IrsA, a novel, iron-regulated exoprotein that facilitates growth in low-iron conditions and modulates biofilm formation - Alberto E. Lopez; Joshua Mayoral; Huaixin Zheng; Nicholas P. Cianciotto (Microbiology Spectrum)
ABSTRACT To discover new factors that are involved in iron acquisition by Legionella pneumophila, we used RNA-Seq to identify the genes that are most highly induced when virulent strain 130b is cultured in a low-iron chemically defined medium. Among other things, this revealed 14915, a heretofore uncharacterized gene that is predicted to be transcriptionally regulated by Fur and to encode a novel, ~15 kDa protein. 14915 was present in all L. pneumophila strains examined and had homologs in a subset of the other Legionella species. Compatible with it containing a classic signal sequence, the 14915 protein was detected in bacterial culture supernatants in a manner dependent upon the L. pneumophila type II secretion system. Thus, we designated 14915 as IrsA for iron-regulated, secreted protein A. Based on mutant analysis, the irsA gene was not required for optimal growth of strain 130b in low-iron media. However, after discovering that the commonly used laboratory-derived strain Lp02 has a much greater requirement for iron, we uncovered a growth-enhancing role for IrsA after examining an Lp02 mutant that lacked both IrsA and the Fe2+-transporter FeoB. The irsA mutant of 130b, but not its complemented derivative, did, however, display increased biofilm formation on both plastic and agar surfaces, and compatible with this, the mutant hyper-aggregated. Thus, IrsA is a novel, iron-regulated exoprotein that modulates biofilm formation and, under some circumstances, promotes growth in low-iron conditions. For this study, we determined and deposited in the database a complete and fully assembled genome sequence for strain 130b.IMPORTANCEThe bacterium Legionella pneumophila is the principal cause of Legionnaires’ disease, a potentially fatal form of pneumonia that is increasing in incidence. L. pneumophila exists in many natural and human-made water systems and can be transmitted to humans through inhalation of contaminated water droplets. L. pneumophila flourishes within its habitats by spreading planktonically, assembling into biofilms, and growing in larger host cells. Iron acquisition is a key determinant for L. pneumophila persistence in water and during infection. We previously demonstrated that L. pneumophila assimilates iron both by secreting a non-protein iron chelator (siderophore) and by importing iron through membrane transporters. In this study, we uncovered a novel, secreted protein that is highly iron-regulated, promotes L. pneumophila’s growth in low-iron media, and impacts biofilm formation. We also identified uncharacterized, IrsA-related proteins in other important human and animal pathogens. Thus, our results have important implications for understanding iron assimilation, biofilm formation, and pathogenesis.